2006
DOI: 10.1002/macp.200600232
|View full text |Cite
|
Sign up to set email alerts
|

Low Conversion 4‐Acetoxystyrene Free‐Radical Polymerization Kinetics Determined by Pulsed‐Laser and Thermal Polymerization

Abstract: Summary: The free‐radical polymerization kinetics of 4‐acetoxystyrene (4‐AcOS) is studied over a wide temperature range. Pulsed‐laser polymerization, in combination with dual detector size‐exclusion chromatography, is used to measure kp, the propagation rate coefficient, between 20 and 110 °C. Values are roughly 50% higher than those of styrene, while the activation energy of 28.7 kJ · mol−1 is lower than that of styrene by 3–4 kJ · mol−1. With known kp, conversion and molecular weight data from 4‐AcOS thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The DRI signal is proportional to polymer concentration, while the LS signal is proportional to the product of polymer concentration and molecular weight and thus is more sensitive to the existence of high-mass components present at low concentrations. Previous homopolymerization studies 2,29 indicated that good agreement between DRI and LS data could be expected if Mark-Houwink parameters used in universal calibration for DRI data and dn/dc value used in LS data analysis are correct. Table 2 lists all the constants required for calculation of GMA k p from PLP/SEC data.…”
Section: Resultsmentioning
confidence: 99%
“…The DRI signal is proportional to polymer concentration, while the LS signal is proportional to the product of polymer concentration and molecular weight and thus is more sensitive to the existence of high-mass components present at low concentrations. Previous homopolymerization studies 2,29 indicated that good agreement between DRI and LS data could be expected if Mark-Houwink parameters used in universal calibration for DRI data and dn/dc value used in LS data analysis are correct. Table 2 lists all the constants required for calculation of GMA k p from PLP/SEC data.…”
Section: Resultsmentioning
confidence: 99%
“…It is very difficult to determine individual rate parameters for the elementary reactions involved in polymer pyrolysis because they are rapid and compete with numerous other reactions [3]. Currently, published experimental values are only available for a few reaction types that occur in polystyrene pyrolysis, with most coming from polymerization experiments [4,5]. The limited availability of experimental rate parameters necessitates the use of estimation methods based on small molecule chemistry and parameter fitting to experimental data within acceptable physical bounds.…”
Section: Introductionmentioning
confidence: 99%
“…The main reaction pathways to particular products can be investigated if the results of a comprehensive mechanistic model, in terms of reaction mechanism and net rates, are carefully evaluated (Poutsma, 2006; Trninić et al, 2016). Therefore, rate parameters values for reactions in pyrolysis of polystyrene are scarcely available in literature (Li et al, 2006). The product spectrum obtained during pyrolysis of waste polystyrene is very simple as compared with the pyrolysis of other polymers, such as polypropylene, polyvinyl chloride and polyethylene (Kruse et al, 2003).…”
Section: Introductionmentioning
confidence: 99%